Teoria e prática: o ensino de ciências da natureza nas escolas da rede municipal de Foz do Iguaçu - Silva, Taiza de Souza Gusmões da (2020)
This research focused on the search for main features of the learning theories that permeate the practices of teachers who teach natural sciences in the early years of elementary school of Foz do Iguaçu Municipality. The main objective was to investigate the strategies used by the teachers in order to teach Nature Sciences subjects in the early years of elementary school. For field data collection, we have opted for the application of a questionnaire that has been already validated, which aims map the pedagogical actions used by the teacher in their classes in terms of some Learning Theories. The research was carried out in municipal schools in the city of Foz do Iguaçu, with the participation of 18 teachers of natural sciences subject for the 3rd years of elementary school, randomly chosen among the city's educational institutions. The data collected were satisfactory, full of meaning and enabled very significant reflections in the search for answers to our research problem and to achieve the established objectives. By considering the analysis of the collected data, we have concluded that 67% of the respondents belong to a group that adopt pedagogical actions aimed achieve a significant teaching, although the interviewees do not necessarily know or do not plan their actions based on a meaningful teaching such as the Theory of Meaningful Learning (MLT). In addition, a second group, formed by 33% of respondents, maintains pedagogical actions based on more traditional teaching, although actions related to MLT are also observed for this group. When drawing a comparative analysis between teachers who belong to different groups, we observe in their responses the reflection of their actions that are often very close, and the difference between their practices is the intensity of the actions used. Thus, taking into account the data analysis, the respondent teachers demonstrated that even if their actions are based on theories of traditional teaching or meaningful learning, their pedagogical actions are not different, that is, it is perceived that even being part of two groups of different respondents they do not have exclusively traditional or exclusively significant actions. Thus, the research showed that most respondents implement pedagogical actions permeated by the meaningful learning theories. These pedagogical actions, when based on a teaching theory such as MLT, can generate learning with more flexibility and longevity making the teaching process more pleasant and less painful. It is expected that the research could contribute with teachers and other professionals interested in improving science teaching practices, and that the results may benefit the student, who is most interested in the teaching process.